Aquatech: Inventory and Work Maintenance Management System for FRI Malaysia: A system for tracking and maintaining work maintenance in the aquarium facilities - Juliana Jaafar; Adilah Adriana Zainuddin (Journal of Computing Technologies and Creative Content, 2022)
Aquatech: Inventory and Work Maintenance Management System is built purposely for the AquaTAR (Aquarium Tunku Abdul Rahman) of Fishery Research Institute of Malaysia (FRI). FRI is an agency located under the Research Department of Fisheries Malaysia that conducts research on fish, aquaculture resources, and ecology. The system hybrids of three different system concepts, i.e., information system, task management system and inventory management system, in a one responsive web application system. Studies have justified that information management helps to increases the productivity of the organisation. However, storing, maintaining, and tracking the essential resources, work tasks, and assets information can be challenging if not done correctly. Relatively, few systems in the market are available to manage the work maintenance of an extensive fishery collection, such as in AquaTAR. Therefore, this study is to design and implement a web-based application for FRI AquaTAR to help organise and manage fish information assets, track the aquarium facilities’ work maintenance, and efficiently supervise the work maintenance. Three users are designed for the system: the administrator, supervisor, and workers. This system was developed using PHP programming language and MySQL database in maintaining the data storage. The project has successfully developed and satisfying all the intended objectives. Questionnaire distributed to 25 participants (6 administrators, 8 supervisors and 11 workers) shows that more than 88% of the participants are satisfied with the functions explicitly provided to their role and more than 80% are satisfied with the system's user interface (UI).